Caprine coccidiosis in semi-arid India: Dynamics and factors affecting fecal oocysts count - Sharma, Dinesh Kumar; Paul, Souvik; Rout, Pramod Kumar; Mandal, Ajoy; Bhusan, Saket; Sharma, Nitika; Kushwah, Yogendra Kumar (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study envisages dynamics and factors affecting fecal oocyst counts (FOC) in natural infection in goats in semi-arid India. Materials and methods: A total of 1152 fecal samples from Jamunapari goats in semi-arid India were collected, processed and examined for fecal oocysts over a period of 3 years for prevalence and severity of the disease through FOC using modified Mc Master Technique. The log transformed FOC data on 912 animals from 59 sires were used for subsequent analyses for genetic and non-genetic factors affecting FOC. Fixed effects included were years of collection (1-3), seasons of collection (summer, rainy, winter), sex (male, female), age group (0-3, >3-6, >6-12, adults). Least squares analysis of variance for fitting constant was applied to data set. Results: The overall prevalence of coccidian infection in goats was 86.71%(n=999/1162). Highest incident was found in winter season (91.74%) and >6-12 M age (97.95%). Eimeria arloingi and E. ninakohlyakimovae were the most frequently occurring species. The heritability of FOC was found to be 0.06±0.06. The effect of sire on FOC was not significant; however, effects of animal age, year, season of collection and sex on FOC were found to be significant. Conclusion: Coccidiosis in goats is seasonally occurring disease, most commonly affecting animals of less than one year age. FOC in coccidiosis affected animals is lowly inherited trait for selection of goat against this disease. http://doi.org/10.5455/javar.2017.d190